Memantine loaded PLGA PEGylated nanoparticles for Alzheimer’s disease: in vitro and in vivo characterization - Elena Sánchez-López; Miren Ettcheto; Maria Antonia Egea; Marta Espina; Amanda Cano; Ana Cristina Calpena; Antoni Camins; Nuria Carmona; Amélia M. Silva; Eliana B. Souto; Maria Luisa García (Journal of Nanobiotechnology, 2018)
Abstract Background Memantine, drug approved for moderate to severe Alzheimer’s disease, has not shown to be fully effective. In order to solve this issue, polylactic-co-glycolic (PLGA) nanoparticles could be a suitable solution to increase drug’s action on the target site as well as decrease adverse effects. For these reason, Memantine was loaded in biodegradable PLGA nanoparticles, produced by double emulsion method and surface-coated with polyethylene glycol. MEM–PEG–PLGA nanoparticles (NPs) were aimed to target the blood–brain barrier (BBB) upon oral administration for the treatment of Alzheimer’s disease. Results The production parameters were optimized by design of experiments. MEM–PEG–PLGA NPs showed a mean particle size below 200 nm (152.6 ± 0.5 nm), monomodal size distribution (polydispersity index, PI < 0.1) and negative surface charge (− 22.4 mV). Physicochemical characterization of NPs confirmed that the crystalline drug was dispersed inside the PLGA matrix. MEM–PEG–PLGA NPs were found to be non-cytotoxic on brain cell lines (bEnd.3 and astrocytes). Memantine followed a slower release profile from the NPs against the free drug solution, allowing to reduce drug administration frequency in vivo. Nanoparticles were able to cross BBB both in vitro and in vivo. Behavioral tests carried out on transgenic APPswe/PS1dE9 mice demonstrated to enhance the benefit of decreasing memory impairment when using MEM–PEG–PLGA NPs in comparison to the free drug solution. Histological studies confirmed that MEM–PEG–PLGA NPs reduced β-amyloid plaques and the associated inflammation characteristic of Alzheimer’s disease. Conclusions Memantine NPs were suitable for Alzheimer’s disease and more effective than the free drug.